"It's a kind of freedom": adolescents and parents speak about motivations for active travel and COVID-19. Issue 1 (31st December 2022) - Levi, Sharon; Baron-Epel, Orna
ABSTRACT: Purpose: Active travel (AT) incorporates physical activity into daily living, critical for healthy adolescent development. We explore adolescent and parent attitudes and behaviours related to motivations for adolescent AT and effects of the COVID-19 pandemic. Methods: We conducted semi-structured Zoom interviews with 25 adolescent-parent dyads in communities across Israel during early stages of the COVID-19 pandemic. Thematic content analysis was used to develop categories and themes. Results: We identified key themes related to adolescent AT: Fostering independence enables adolescent AT; Pampering and safety concerns inhibit adolescent AT; Family and community norms influence adolescent travel modes; Personal enjoyment and positive attitudes facilitate AT; Peers and social networks promote adolescent AT and PA; Built environment and transport options influence AT choices. Interestingly, adolescents indicate AT is an opportunity for peer-to-peer communication without screen distraction, yet they use social media to promote AT and PA. Conclusions: The findings point to the influence of positive parent perceptions, active and supportive family and community norms on adolescent AT. Peer norms and social networks as well as features of the built environment also have the potential to influence AT. The COVID-19 pandemic encouraged use of AT and provided a setting for positive AT experiences.